Policy options and their potential effects on Moroccan small farmers and the poor facing increased world food prices: A general equilibrium model analysis - Diao, Xinshen; Doukkali, Rachid; Yu, Bingxin (International Food Policy Research Institute, 2008)
This study evaluates the potential impact of the recent rise in world food prices on the Moroccan economy and possible policy options to respond to it. The study focuses mainly on the poverty effects of such an external shock and the possible policy responses to it. A new social accounting matrix (SAM) and a computable general equilibrium (CGE) model have been developed for this study based on micro-level data in combination with sectoral and economywide data. The CGE model simulations show that while increased world food prices hurt poor consumers, the general equilibrium effect of welfare loss is modest. Agricultural producers gain, and benefits to small farmers are especially large. The simulation of import subsidies shows that while such policy options can temporarily stabilize domestic prices, the benefits to consumers are at the expense of producers. However, the model results indicate that there are win-win options for Morocco if policies are based on a longer-term objective. Direct transfers to poor consumers, combined with increased public investment in agriculture to improve agricultural productivity, is a win-win strategy that the government should consider. Low productivity in staple crop production is the dominant reason for poverty among Moroccan farmers. Improving this productivity can also benefit poor consumers by lowering domestic food prices.